(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction Health information systems (HIS) are integral to enhancing the quality and efficiency of healthcare delivery. These systems support pharmacists in managing medication therapy, improving patient safety, and facilitating better communication within healthcare teams. Despite their potential to revolutionize patient care, the adoption and effective use of HIS among pharmacists are often hindered by various challenges. Previous studies have highlighted the benefits of HIS, including improved medication management and streamlined workflows. However, the extent of pharmacists’ knowledge about HIS and their perceptions regarding its implementation and impact on patient care remains underexplored. This study aims to fill this gap by evaluating the current level of knowledge and perceptions among pharmacists at University College Hospital (UCH), Ibadan, Oyo State, and identifying barriers to the effective use of HIS in enhancing patient care. Objective To assess the level of knowledge and perception of pharmacists about HIS, identify barriers to its effective utilization, and explore its effects on patient care. Method of Analysis A cross-sectional survey was conducted among pharmacists at UCH. Data were collected using a structured questionnaire designed to assess knowledge, perceptions, and potential barriers related to HIS. Descriptive and inferential statistics were used to analyze the data, including frequencies, percentages, and correlation analyses. Results The study found that 79.2% of pharmacists reported a high level of knowledge about HIS. The majority (90.8%) perceived HIS as beneficial for both patients and themselves, with 90% acknowledging that training improves patient well-being. However, barriers to effective utilization were identified: 52.5% of pharmacists cited insufficient training, 45.8% reported a lack of drug information resources, and 64.2% pointed to a lack of perception and practice-related issues. Financial constraints were also noted, with 52.5% of respondents indicating a lack of adequate funds. Conclusion Pharmacists at UCH demonstrate a high level of knowledge and positive perception of HIS, recognizing its benefits in patient care. However, significant barriers, including insufficient training, lack of resources, and financial constraints, impede the effective utilization of these systems. Addressing these barriers through enhanced training, improved resource availability, and better funding could facilitate more effective integration of HIS into pharmacy practice, ultimately improving patient outcomes.